Affective States: A Neglected Construct in the Study of Efficacy - Hoogsteen, T.J. (Advances in Social Sciences Research Journal, 2024)
The social cognitive theory concept of efficacy has a rich evidence base to support its importance to educators. Although there is much research in support of the theory, there is also evidence which contradicts some of its major and long-held beliefs. One of these beliefs is that out of the four sources of efficacy, affective states are the weakest in terms of impact. This paper synthesizes evidence to challenge the accepted notion and presents an argument for affective states being the most powerful source of efficacy. This idea has important implications for school leaders because of efficacy’s relationship to resilience and job commitment.